Improving construction design : The lean thinking paradigm - Morris, Jonathan (Cranfield University, 1999)
A study has been conducted into improving construction design through the application of the lean thinking paradigm. Its objective was to identify the issues relating to design efficiency and how a lean thinking approach might address these issues. The investigation consisted of examining work already undertaken in the field by other researchers"to identify the state of the art. The change order request system was examined to gain first insights into waste in construction design, and to gauge the size of the opportunity for the application of lean thinking. An Electronic Data Gathering Tool (EDGT) was then developed to allow further exploration of the design decision making process at the system / sub-system level. The EDGT was used on three live construction projects. From the data recorded a design planning tool, Design Decision Planner (DDP), was created to help improve control of the design process and lead to a more standardised approach to construction design. Standardising the approach to product development is an important component of lean thinking. The main recommendations for making construction design lean are: Use DDP to plan and improve control of the design decision making process, assign design responsibility and to make the process more transparent. 2. Measuring progress against planned design is a useful process metric. 3. Improve the designer's cost and programme visibility when choosing between design options. 4. Redefine the role of the quantity surveyor from cost controller to value for money assessor. The role needs to be better integrated into the design process to reach its full potential. 5. Need to develop more rigorous methods of assessing the buildability of design options. This problem could be eased in the short-term by incorporating construction professionals into the early design phases. 6. Designers need to use more process reason drivers when choosing between design options, not just functional criteria. 7. The change order request system could be redesigned to identify the root causes of contract issue design changes and, hence, improve the design decision making process.